The role of pure and occupied fallows in increasing of winter wheat productivity and conservation of soil fertility - G. V. Ovsyannikova; N. G. Jankowski; E. D. Krivosheeva (Аграрная наука Евро-Северо-Востока, 2016)
The results of research on the influence of predecessors and long-term application of fertilizers on productivity of winter wheat and the balance of humus in field crop rotation are presented in the article. Predecessors of winter wheat were pure and occupied (sainfoin) fallows. Mineral and organic fertilizers were entered on the pure fallow predecessor with plowing. During the growing season nitrogen fertilization was applied. Only nitrogen fertilization was used on sainfoin predecessor. Studies have shown that the application of fertilizers for winter wheat on the pure and sainfoin fallows contributed to the increase in the content of nutrients in the soil throughout the growing season and the formation of additional grain yield. Additions of productivity on the fertilized variants were 0.59-1.08 t/ha on pure fallow and (control - 4.96 t/ha); on sainfoin - 0.56-0.80 t/ha (control - 3.91 t/ha). This allows to use occupied fallow (sainfoin) in the zone of unstable humidification in addition to the pure fallow as well as instead of pure fallow obtaining the grain yield of winter wheat in the range of 3.91-4.71 t/ha. At entering of green manure fallow into the crop rotation without manure application processes of humification in the soil prevail over the processes of mineralization. The flow of organic matter in the form of green manure (sainfoin) can stabilize the humus content in the soil (humification - 8.20, mineralization - of 7.95 t/ha). Application of mineral fertilizers provides an additional flow of organic matter to the soil. On average, the crop rotation has a positive balance of humus - 1.15-1.16 t/ha.